Cataract complications - David Yorston (Community Eye Health Journal, 2008)
Any eye surgeon, no matter how experienced, will occasionally encounter a serious cataract complication. Although complications may be devastating for the patient and are always distressing for the surgeon, are they really a major issue for VISION 2020? The evidence says that they are.